The influence of aquatic humic substances from an area of sugarcane and orange on the dynamics of chromium ions in the environment - Tadini, A. M. [UNESP]; Moreira, A. B. [UNESP]; Bisinoti, M. C. [UNESP] (Springer Nature, 2012)
The northwest region of São Paulo State is a typical agricultural region with crops of sugarcane and oranges predominating, being chromium ions of environmental interest. Studies of the role of aquatic humic substances (AHS) in the transport of chromium ions in aquatic bodies are practically nonexistent. In this context, this work aimed to assess the influence of AHS from an area of sugarcane and orange on the dynamics of chromium ions (Cr+3 and Cr+6) in the environment. AHS were extracted in accordance with the method suggested by the International Humic Substances Society, followed by fractionation into different molecular sizes (<10, 10-30, 30-50, 50-100 and >100 kDa). AHS were characterized by UV/Vis, molecular fluorescence and IR. Complexation capacity (CC) of AHS with ions Cr+3 and Cr+6 was performed employing the system of tangential-flow ultrafiltration with membranes of 1.0 kDa. AHS showed a higher degree of aromaticity and predominance of the humic acids. We can conclude that the fraction F1 (<10 kDa) and F2 (10-30 kDa) showed the higher CC with Cr+3 ion (2.15 mmol Cr+3 g-1 carbon) and Cr+6 ion (4.61 mmol Cr+6 g-1 carbon), respectively.
Keywords: Aquatic humic substances; Complexation; Metals